THE IMAGE OF WOMAN IN COMMUNICATION MEDIA: . - Teekoy, Mathew C (Journal of Dharma, 1991)
Communication Media acts as a mirror, in imaging the concerns, conceptions, capacities and aspirations as well as the problems, catastrophes and evils of a society. It also moulds, focuses and accelerates public opinion about issues and events. It is a well known dictum that the media creates and destructs images of societies, peoples and persons. Hence it is worth studying how the contemporary Communication Media projects the woman of India and how it represents her problems, aspirations and concerns.